Art editions 3 : Edition Schellmann (München : Edition Schellmann, 2001)
Arakawa, Shusaku ; Armstrong, David ; Artschwager, Richard ; Baechler, Donald ; Barney, Matthew ; Baselitz ; Baumgarten, Lothar ; Becher, Bernd und Hilla ; Beecroft, Vanessa ; Beuys, Joseph ; Boltanski, Christian ; Broodthaers, Marcel et al.
boek